Peran Pendidikan Kewarganegaraan di Era Globalisasi Dalam Pembentukan Karakter Siswa - Siti Humaeroh; Dinie Anggraeni Dewi (Departement of Mathematics Education, 2021)
Science and technology are experiencing rapid developments marking the entry of globalization in a country. Globalization has had a major impact, both positive and negative. This globalization affects the lifestyle of the westernized society and reduces the values ​​and nationalism of the Indonesian nation. Education is one of the most effective ways to build good character for the younger generation. This research was conducted using qualitative data collection. It is found that character education has a function as a vehicle for development, improvement, and filter. In addition, character education has other functions, namely developing potential, habits, and behavior, fostering leadership and responsibility, developing abilities and the school environment. Citizenship education has functions including building participatory skills that make Indonesian citizens active, critical, intelligent, and democratic, as well as building a civilized democratic culture. Based on the research, the suggestion that can be given is that there is a need for the involvement of all parties in paying attention and participating in building the character of students as the future generation of the Indonesian nation